'You'll never walk alone': Supportive social relations in a football and mental health project. (11th February 2015) - McKeown, Mick; Roy, Alastair; Spandler, Helen
Abstract Football can bring people together in acts of solidarity and togetherness. This spirit is most evocatively illustrated in the world renowned football anthem 'You'll Never Walk Alone' (YNWA). In this paper, we argue that this spirit can be effectively harnessed in nursing and mental health care. We draw on data from qualitative interviews undertaken as part of evaluating a football and mental health project to explore the nature of supportive social relations therein. We use some of the lyrics from YNWA as a metaphor to frame our thematic analysis. We are especially interested in the interactions between the group facilitators and group members, but also address aspects of peer support within the groups. A contrast is drawn between the flexible interpersonal boundaries and self‐disclosure evident in the football initiative, and the reported, more‐distant relations with practitioners in mainstream mental health services. The findings suggest scope for utilizing more collective, solidarity‐enhancing initiatives and attention to alliances and boundaries to maximize engagement and therapeutic benefits within routine practice.